Obtaining carbon nanoparticles from biomass and its application in the preparation of nanofluids for combustion in diesel engines (2023)
ABSTRACT: Energy is a key factor in the economic and social development of countries, but also a challenging issue. Internal combustion engines are widely utilized in heavy and light vehicles, being the main users of fossil fuels.